SPE Annual Technical Conference and Exhibition 2008
DOI: 10.2118/115653-ms
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Gel Cleanup in a Propped Fracture With Dynamic Fracture Conductivity Experiments

Abstract: The effect of residual fracture fluid gels on the conductivity of propped fractures has commonly been measured in the laboratory with a static fracture conductivity procedure in which a certain amount of proppant is placed in a fracture conductivity cell, and then fracture fluid is injected into the cell. This test does not capture all of the physics of the process of proppant placement and fracture closure as it occurs in an actual fracturing treatment. In particular, the interactions among the transport of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Classification of polyelectrolytes in terms of their charge, Koets and Kosmella [36] .... 19 Figure 10 Simplified illustration of the surface and zeta potential for a charged suspension drop dispersed in high (saline water) and low (fresh water) electrolyte concentration aqueous solution [37] .. [28,43] Figure 19 Tertiary structure of proteins [28,43] Quaternary structure of proteins [28,43] Schematic picture for catalytic reaction of enzymes [28,43] Figure 25 Comparing the viscosity reduction obtained by a commercial enzyme and a hightemperature enzyme (Tayal et al) [58] Vitthal [61,62] Figure 38 Schematic of a disassembled 175 mL static fluid loss cell presented by Asadi et al [69] See page 64 (Marpaung et al) [80] . (Barati et al) [7] ... pore volume injected [93] .…”
Section: List Of Figuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Classification of polyelectrolytes in terms of their charge, Koets and Kosmella [36] .... 19 Figure 10 Simplified illustration of the surface and zeta potential for a charged suspension drop dispersed in high (saline water) and low (fresh water) electrolyte concentration aqueous solution [37] .. [28,43] Figure 19 Tertiary structure of proteins [28,43] Quaternary structure of proteins [28,43] Schematic picture for catalytic reaction of enzymes [28,43] Figure 25 Comparing the viscosity reduction obtained by a commercial enzyme and a hightemperature enzyme (Tayal et al) [58] Vitthal [61,62] Figure 38 Schematic of a disassembled 175 mL static fluid loss cell presented by Asadi et al [69] See page 64 (Marpaung et al) [80] . (Barati et al) [7] ... pore volume injected [93] .…”
Section: List Of Figuresmentioning
confidence: 99%
“…Marpaung et al [80] , Chen et al [81] and Zou et al [82] presented a dynamic conductivity cell similar to that of Much and Penny [79] and Penny [78] to compare the results traditionally presented using static conductivity cells with the dynamic results using wet gas to clean up the broken fracturing fluids from the proppant pack. Using the setups presented in Figure 47 and Figure 48 for fluid loss and cleanup of fluid they reported that the measured conductivity using the static conductivity cells is much higher than that measured using the dynamic cells.…”
Section: Figure 46 Flow Effects On Filter Cake Using Different Dynamimentioning
confidence: 99%
“…Modifications to the API/ISO recommended testing apparatus and operational procedures have been made for specific applications (Marpaung et al, 2008). A modified API conductivity cell is 10 inches long, 3.25 inches wide, and 8 inches in height.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made to modify existing API fracture conductivity test cell [Marpaung et al, 2008;Zhang et al, 2013],…”
Section: Introductionmentioning
confidence: 99%